Design and test of a double compression seeder for pre-sowing and seed furrow of wheat in wide-seedling belts - He, Xun; Zhang, Run; Zhang, Jingfeng; Zhu, Yinghao; Wang, Wanzhang; Zhang, Hongmei (International Journal of Agricultural and Biological Engineering, 2024)
To solve the problem of poor sowing quality due to loose soil in wheat seedbed after land preparation in the Huang-Huaihai region of China, a double compression seeder for pre-sowing and seed furrow of wheat in wide-seedling belts was designed. The machine sowing operation was divided into two processes: pre-sowing compression and seed ditch compression, pre-sowing compression was carried out homogenization of the pre-sowing seed bed that the tractor wheel has crushed, and the seed ditch compression compresses the seeds and soil in the seed ditch, so that the seeds were embedded in the seed ditch soil. By analyzing the kinematics of the pre-planting compression device and the spiral blade in the process of soil levelling and compression, the structure of the equal-difference variable-diameter equal-pitch spiral conveying winch was designed, and the key parameters of the drum spiral blade were determined, and then the height of the spiral blades, the rutting distance and the speed of the compression roller were taken as the test factors, and the soil flatness was used as the index to carry out the discrete element simulation test. The simulation results show that when the spiral blade was 4.85 cm, the rut distance was 37.4 cm, and the rotation speed was 327.16 r/min, the optimal land flatness was 0.18. Finally, field experiments were carried out on the seeder, and the results showed that: the soil bulk density after operation was 22.7% greater than that before sowing (p < 0.01), and the soil flatness was 1.9 cm, which was consistent with the simulated results. The use of pre-sowing compression and seed furrow compression methods improved the soil environment of the seed bed, increased the uniformity of the seeding depth, and promoted the root growth of wheat. This study provides equipment support and technical reference for agricultural production in wheat-corn rotation areas in the Huang-Huaihai region of China. Key words: wheat; seeding quality; pre-sowing compression; seed furrow compression; field experimentDOI: 10.25165/j.ijabe.20241704.8369Citation: He X, Zhang R, Zhang J F, Zhu Y H, Wang W Z, Zhang H M. Design and test of a double compression seeder for pre-sowing and seed furrow of wheat in wide-seedling belts. Int J Agric & Biol Eng, 2024; 17(4): 136–145.